The urgency of developing trust and interpersonal communication skills of students through role playing - Sari, Yulia Novita (Universitas Negeri Padang, 2018)
Students as social beings cannot be separated from various activities that involve other people. Related to this need, interaction becomes a decisive part. The most important element in interacting is having good self-confidence and interpersonal communication skills. The problem of self-confidence and students’ interpersonal communication skills has become more widespread. Role playing is one of the right techniques used to overcome this problem. This technique aims to prepare students to take on the role of people, to develop insights about unspoken attitudes, thoughts, and feelings, which often determine the behavior of others, and to increase self-confidence and communication skills through student participation in implementing challenges communication faced. This text will explain how the urgency of developing self-confidence, and interpersonal communication can be developed through role playing.